Critical Appraisal of Studies Conducted in the Department of Periodontics, Mashhad School of Dentistry, in the Last Twenty Years (1994-2014) - Majid Reza Mokhtari; amir moeintaghavi; Hamid Reza Arab; sabete bagheri sabzevar (Mashhad University of Medical Sciences, 2021)
Critical appraisal of research studies is an essential process in quality assessments and development, in which various aspects of a subject are carefully analyzed. In recent decades, many articles have been published in medical journals especially in dental field, without being officially criticized. Citing results of these epidemiological studies requires proper validation. The validation is performed through 'critical appraisal' according to standard criteria and checklists. In this paper, 81 studies conducted between 1994 and 2014 in periodontics field in dentistry were divided into five categories: observational studies, diagnostic, clinical, animal, and meta-analysis, and reviewed by STROBE, STARD, CONSORT, ARRIVE, PRISMA Checklists. In most studies, participants' characteristics and inclusion and exclusion criteria were mentioned. In most studies, random sampling was not performed without bias. It is hoped that in future studies, researchers will use standard checklists from the initial stages of the study to obtain valid and scientific results.